Alternating Stacked Graphene‐Conducting Polymer Compact Films with Ultrahigh Areal and Volumetric Capacitances for High‐Energy Micro‐Supercapacitors. (3rd June 2015) - Wu, Zhong‐Shuai; Parvez, Khaled; Li, Shuang; Yang, Sheng; Liu, Zhaoyang; Liu, Shaohua; Feng, Xinliang; Müllen, Klaus
<x xml:space="preserve">Abstract</x> Graphene‐based compact nanohybrid films made by alternate deposition of electrochemically exfoliated graphene and mesoporous graphene‐conducting polymer nanosheets are constructed for high‐energy micro‐supercapacitors. They are shown to have a landmark areal capacitance of 368 mF cm−2 and volumetric capacitance of 736 F cm−3.